2008
DOI: 10.1080/14765280802283576
|View full text |Cite
|
Sign up to set email alerts
|

Openness, human capital and total factor productivity: evidence from China

Abstract: This paper examines the drivers behind China's economic growth. In particular, it focuses on the channels of knowledge spillovers: human capital and openness to trade and foreign direct investment. The specific features of the study include using the most recent comprehensive panel data consisting of 29 provinces during the period 1994-2006 and performing unit root and cointegration tests in the panel data framework. The paper finds that human capital, trade and FDI are the significant determinants of total fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 23 publications
7
21
0
Order By: Relevance
“…The varying impacts of FDI via the three channels on economic growth across regions in China further highlights the importance of locational factors in influencing economic growth in the CEI. These findings are similar to that of Liu and Wang (2003) for China, who found that locational factors are necessary for enhancing FDI spillover effects on economic growth, and Xu et al (2008) who concluded that FDI yields distinct effects on economic growth across different regions in China. Overall, the empirical results indicate that foreign capital has a positive impact on economic growth across the coastal, central and western regions in China.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The varying impacts of FDI via the three channels on economic growth across regions in China further highlights the importance of locational factors in influencing economic growth in the CEI. These findings are similar to that of Liu and Wang (2003) for China, who found that locational factors are necessary for enhancing FDI spillover effects on economic growth, and Xu et al (2008) who concluded that FDI yields distinct effects on economic growth across different regions in China. Overall, the empirical results indicate that foreign capital has a positive impact on economic growth across the coastal, central and western regions in China.…”
Section: Resultssupporting
confidence: 89%
“…Although the theoretical literature predicts that FDI inflows could create knowledge and productivity spillover for the FDI-recipient country, the empirical evidence on the FDI-growth nexus is rather mixed. Many researchers attribute the mixed results to differences in absorptive capacity across FDI-recipient economies (see Todo and Miyamoto, 2006;Liu and Buck, 2007;Kuo and Yang, 2008;Xu et al, 2008). For Chen et al (2011), the effect of FDI spillover effects on economic growth in a country depends on the interaction between foreign firms and domestic ones.…”
Section: The Relationship Between Fdi Locational Factors and Ecomentioning
confidence: 95%
See 2 more Smart Citations
“…The coefficients of all alternative measures of human capital are strongly statistically significant in all of the regressions. The findings of this study align with several earlier findings (Welch 1970;Schultz 1975;Romer 1990;Benhabib et al 1992;Miller and Upadhyaya 2000;Goldar et al 2003;Siddharthan and Lal 2003;Apergis et al 2008;Xu et al 2008;Kathuria 2013). Country-specific studies-such as Kathuria (2013) (for India), and Xu et al (2008) and Wei and Hao (2011) (for the PRC)-prove that human capital is a crucial factor of productivity growth.…”
Section: Empirical Evaluation Of the Structural Change Effect On Labosupporting
confidence: 91%